Peak coffee? Die Folgen des Klimawandels für Arabica Kaffee: Presentation at Kaffeeröster-Tagung - Hamburg, Germany - Lundy, Mark M.; Bunn, Christian (2016)
What are the risks that the coffee sector faces from climate change and what can be done to minimize those risks. Focus on telling a simple story for an industry audience.